Anthropometric characteristics of elite male junior rowers - Chinchilla Mira, J. J.; Perez-Turpin, J.; Cortell-Tormo, J. M.; Cejuela, A. R. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
During the preparation stage for a junior regional team (from the Comunidad Valenciana region, Spain), the anthropometric characteristics were collected from 18 male junior rowers, aged 17,83±3,83. An anthropometric study was carried out on the rowers, using a technique based on Carter (1976) and the protocol of The International Society for the Advancement of Kinanthropometry (ISAK). The rowers were assessed in order to describe an updated athropometric profile of elite junior male rowers. Anthropometric studies have often been performed on junior rowers (Bourgois, J et al., 2001: Journal of Sports Sciences, 19, 195-202) in order to analyze their evolution into senior category. However, information on present parameters is still limited. The purpose of the descriptive study was to identify the present anthropometric assessment of elite male rowers in Spain. 18 rowers from the team were included in this study, using the Holtain skinfold caliber, the Holtain bone diameter caliber, scales, stadiometer and anthropometric tape. The measurements for each rower included weight, height, BMI, muscle mass, fat mass, bone mass and residual mass. After the measurements, the statistical analysis was performed by means of the SPSS 13.0 package, in order to compare the data for the rowers. The first result showed that the weight was 76,47± 9,42 kg, height 178,93± 7,66 cm, BMI 23,78± 1,42 kg/T2, muscle mass 34,16± 2,74 kg, fat mass 12,06± 3,05, bone mass 12,56± 1,32 and residual mass 17,67± 3,49. An improved knowledge of the anthropometric data for junior rowers is very important in order to set specific training patterns for rowing. The results suggest that this study could widen the knowledge on rowers` parameters.